Cytodiagnosis of Extramedullary Leukemic Infiltration: A series of Nine Cases - Swati Diwakar; Gunja Dwivedi; Priya Parmar; Anju Mishra (International Journal of Scientific Research in Dental and Medical Sciences)
Nine cases of extramedullary leukemic infiltration were examined using fine-needle aspiration cytology (FNAC), focusing on clinical presentations, cytological findings, and hematological diagnoses. The cases included chronic myeloid leukemia (CML) and acute leukemia, with extramedullary sites such as lymph nodes, skin, pleural fluid, and soft tissue affected. FNAC smears commonly showed scattered granulocytic precursor cells, blasts, and mature neutrophils. One case presented with malignant pleural effusion. The cytological features helped distinguish leukemic infiltration from lymphoma, although challenges arose when FNAC was used without considering the full hematological context. The study concluded that extramedullary leukemic infiltration can occur at various stages and locations, and FNAC is an effective diagnostic tool when combined with peripheral smear examination and patient history. This emphasizes the importance of comprehensive monitoring and interdisciplinary collaboration for accurate diagnosis and treatment planning in these cases.